Study of seizures among pediatric age group (0-12 years) in tertiary health care center of a district of Maharashtra, India - Miyan Tambe, Saleem Hussain; Ali Inamdar, Ismail Ali Farukh; Bari, Nasir Abdul; Chavan, Arvind Nilkanthrao (International Journal of Contemporary Pediatrics, 2017)
Background: Seizures represent the most distinctive signal of neurological disease in the newborn period and these convulsive phenomena are the most frequent of the overt manifestation of neonatal neurological disorders. Recognition and classification of seizures remain problematic; particularly when pediatricians rely only on clinical criteria. The objective of this study was to study the incidence of pediatrics (0-12 years) seizures. To study the etiology and pattern of seizures. Methods: 326 Subjects who had seizures were included in the study. Relevant history was ascertained from a patient’s parents or a reliable relative or attendant, medical records and the referring physicians note, specifically from mother in case of neonatal seizures i.e. age at onset of seizures, seizure activity with special emphasis on occurrence of 1st seizures, duration of seizures, number and type of seizures, associated autonomic changes, medications required to control seizures, response time to medications, and possible causes for determination of etiology. A detailed antenatal, natal and postnatal history was taken. Results: Out of 326 study subjects 117 (35.89%) were in neonatal age group, of which 75 (64.10%) and 42 (35.90%) were male and female respectively and 209 (64.11%) were beyond neonatal age, out of which 125 (59.8%) were male and 84 (40.2%) female. out of 117 neonatal seizures, 75 (64.10%) neonates were male and 42 (35.90%) were female. Male: Female ratio was 1.79:1. The seizures were common in male neonates. Subtle seizures were the commonest type of seizures observed both in term and preterm neonates. Conclusions: The various types of seizure were compared with the preterm and term neonates and it was found statistically significant (X2 = 5.06 d.f. = 4, p<0.05). The various causes of seizure were compared with the preterm and term neonates and it was found statistically significant (X2= 17.42 d.f. = 6 p<0.05).